Formative assessment in practice: Children’s experiences in Maldivian classrooms - Mohamed, Niuma; Fastier, Murray (Journal of Research, Policy & Practice of Teachers and Teacher Education, 2018)
Assessment practice in Maldivian schools is currently undergoing change. The new draft Maldivian National Curriculum (Education Development Centre, 2012a) and associated documents aim to align assessment, instruction, and curriculum in an effort to optimize learning conditions for students. The support document entitled ‘Pedagogy and Assessment Guide a Working Document’ highlights the importance of ensuring a balance between assessment ‘for’ learning (formative assessment) and assessment ‘of’ learning (summative assessment). Maldivian teachers, who have traditionally placed emphasis on summative assessment practice, will now be required to enhance their use of formative assessment strategies to help diagnose individual student’s strengths and weaknesses and to support future learning. The focus of this article is to identify formative assessment practices Maldivian students may already be experiencing in the lower primary school grades 1to 3.